2006
DOI: 10.5172/conu.2006.21.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of registered psychiatric nurses towards patients diagnosed with borderline personality disorder

Abstract: Caring for patients with a diagnosis of Borderline Personality Disorder (BPD) has been identified as a problem area for mental health professionals with some studies suggesting that a diagnosis of BPD will influence the level and quality of interaction staff have with patients. It is inherent to psychiatric nursing that practitioners are able to establish rapport, develop trust and demonstrate empathy with consumers of mental health services. Despite the importance of this issue for psychiatric nurses and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 14 publications
2
77
1
3
Order By: Relevance
“…The research indicates that health staff tend to have strong reactions to this diagnosis, with more negative attitudes (compared to various other psychiatric diagnoses) and with less empathy (Fraser & Gallop 1993;Markham 2003;Filer 2005;Aviram et al 2006;Deans & Meocevic 2006;Commons Treloar & Lewis 2008a;Westwood & Baker 2010;Black et al 2011). …”
Section: Stigma and Negative Attitudesmentioning
confidence: 95%
See 1 more Smart Citation
“…The research indicates that health staff tend to have strong reactions to this diagnosis, with more negative attitudes (compared to various other psychiatric diagnoses) and with less empathy (Fraser & Gallop 1993;Markham 2003;Filer 2005;Aviram et al 2006;Deans & Meocevic 2006;Commons Treloar & Lewis 2008a;Westwood & Baker 2010;Black et al 2011). …”
Section: Stigma and Negative Attitudesmentioning
confidence: 95%
“…Others discuss how the symptoms and behaviour associated with BPD may lead to strong emotional reactions from healthcare staff (Gallop et al 1989;Deans & Meocevic 2006;Commons Treloar & Lewis 2008a). One part of BPD diagnostic criteria is intense, unstable relationships and conflict (American Psychiatric Association 2000, 2013.…”
Section: Reasons For Stigmamentioning
confidence: 99%
“…On the contrary, in daily practice it is often associated with long-term care lacking clear aims and therapeutic ambitions, 10 possibly resulting in unnecessary dependency. In addition, negative professional attitudes towards patients with personality disorders have been reported frequently, [11][12][13] possibly resulting in an ineffective patient-professional interaction, especially in long-term supportive care. Therefore, we aim to answer the following questions in this review: what, exactly, is CMHC for severe personality disorder; who provides it; how does it compare with other forms of treatment for this disorder; what are its empirical and theoretical underpinnings; and what are its strengths and limitations?…”
mentioning
confidence: 99%
“…Lewis and Appleby (1988) gave 173 psychiatrists case vignettes of patients diagnosed with PD or not, and found that the PD patients were seen as manipulative, attention seeking, annoying, and in control of their suicidal urges. Deans and Meocevic (2006) studied 65 registered nurses with at least one year's experience in services treating patients with a diagnosis of borderline PD (BPD). Their 50-item questionnaire examined nurses' clinical descriptions of patients with BPD, their emotional reactions, concerns and opinions about management.…”
mentioning
confidence: 99%